2020
DOI: 10.1186/s12889-020-8288-6
|View full text |Cite
|
Sign up to set email alerts
|

Diet, physical activity, and emotional health: what works, what doesn’t, and why we need integrated solutions for total worker health

Abstract: Background: Current research advocates lifestyle factors to manage workers' health issues, such as obesity, metabolic syndrome, and type II diabetes mellitus, among other things (World Health Organization (WHO) Obesity: preventing and managing the global epidemic, 2000; World Health Organization (WHO) Obesity and overweight, 2016), though little is known about employees' lifestyle factors in high-stress, high turnover environments, such as in the long term care (LTC) sector. Methods: Drawing on qualitative sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
2
23
0
2
Order By: Relevance
“…The daily energy needs of a worker depend on many factors such as anthropometrics, job, environment, and hours of work [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The daily energy needs of a worker depend on many factors such as anthropometrics, job, environment, and hours of work [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canadian studies of immigrants, racialized workers, and women suggest that these groups are often predisposed to high stress, chronic illness [ 32 , 33 , 34 ], and difficulties in managing domestic duties [ 35 ] due to work precarization [ 36 ], which adversely affects their health and well-being [ 33 ]. In addition, research has shown that in the care-work sector, many of these employees experience work hierarchies and strict divisions of labor [ 37 ], while utilizing various mechanisms to regulate emotional health [ 38 ]. This study confirms previous research about stress in LTC and reveals new information about stress management techniques, which may help to achieve or maintain workers’ social, mental, and physical well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Another policy option is to minimize stress at its root cause rather than treating stress. For example, workers may be experiencing stress because of the underlying issues of food insecurity, which has been previously reported in the care work literature [ 38 ]. Finally, income, employment, and working conditions are SDoH [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data fitting from the real data of COVID-19 obtained from Chinese Sina-microblog can identify the different contact rates and forwarding probabilities and can be used to evaluate the roles of opinion leaders in different stages of the information propagation and the outbreak unfolding. Early detection of large-scale infectious diseases and understanding of people's ability to respond to these diseases are the concerns of governments around the world [ [23] , [24] , [25] ]. During an epidemic, research on public knowledge, attitudes, and behaviors can refer not only to the formulation of communication and sentiment mitigation strategies but also to the help with future prevention plans [ 26 , 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%